ANALISIS EFEKTIVITAS, PERTUMBUHAN, DAN KONTRIBUSI PAJAK REKLAME TERHADAP PENERIMAAN PAJAK DAERAH PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH (BPPRD) KABUPATEN MUSI BANYUASIN - Candra Romanda; Jumania Septariani (Institut Rahmaniyah Sekayu, 2026)
This study aims to analyze the effectiveness, growth, and contribution of Advertisement Tax to Local Tax revenue at the Regional Tax and Retribution Management Agency (BPPRD) of Musi Banyuasin Regency for 2020–2025. The research method used is descriptive quantitative. The data used consist of primary and secondary data obtained through interviews, documentation, and literature review. Data analysis techniques were carried out using effectiveness ratio analysis, growth ratio analysis, and contribution ratio analysis. The results show that the effectiveness level of Advertisement Tax during 2020–2025 averaged 112.02%, which is categorized as very effective, although it experienced a decline in the final years of the study. The growth ratio of Advertisement Tax averaged 19.81%, which is categorized as unsuccessful, because it fluctuated with increases and decreases in revenue each year. Meanwhile, the contribution ratio of Advertisement Tax to Local Tax revenue averaged 1.67%, which is categorized as very low, indicating that Advertisement Tax has not made a significant contribution to Local Tax revenue in Musi Banyuasin Regency. Based on these findings, BPPRD of Musi Banyuasin Regency is expected to improve data collection, supervision, and taxpayer compliance so that Advertisement Tax revenue can be optimized and contribute more significantly to Local Tax revenue.